Characterisation of the cytokinin-mediated biocontrol activity of Chlamydomonas reinhardtii against Pseudomonas syringae in tobacco and analysis of its potential as a bio-stimulant - Paul, Bichitra (2019)
Dissertação de Mestrado em Ecologia apresentada à Faculdade de Ciências e Tecnologia